Swearing Words in "Euphoria" Television Show Sociolinguistic Study - Bagas Rezka Ginanjar; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to examine and interpret the swearing words in the "Euphoria" series, as well as the series types and functions. The study used descriptive qualitative techniques, such as data analysis and narrative presentation of the findings. The data was taken from the “Euphoria” television series season one. The results of the study are There are 100 data found in the “Euphoria” television series. There are types of swearing words are related to Sex (50data), 50% and then it serves five functions, related to Excrement (22data), 22% and then it serves five functions, related to Animal (10data), 10% and then it serves three functions, related to Personal Background (7data), 7% and then it serves one functions, related to taboo or religion or oath (3data), 3% and then it serves one functions, related to Mental Illness (6data), 6% and then it serves two functions and types of swearing words related to Racism (2data), 2%. and then it serves two functions Additionally, there are five functions of swearing words that are represented by a type of swearing word in the “Euphoria” tv series. Cathartic Swearing 16%, abusive swearing 32%, emphatic swearing 12%, idiomatic swearing 32%, and Dysphemistic Swearing 6%. As a result, this data is dominated by related to sex for types of swear words by 50 % and the same result in the function of swear words, namely abusive and idiomatic at 32%